OMENTAL INFARCTION IN A CHILD - Siddiqui, Saad; Ahmed, Anwar; Nadeem, Naila (Journal of Ayub Medical College Abbottabad, 2016)
Omental infarction is a rare cause of acute abdomen in children. Typical findings on imaging establish the diagnosis. We present case of a 7 years old boy who presented with acute right iliac fossa pain with diagnosis of omental infarction on imaging and findings confirmed on laparotomy. Sound knowledge regarding this infrequent cause of acute abdomen in children is necessary for timely diagnosis. Keywords: Tuberculosis; Computed Tomography; Stomach.